Smallholder livestock production in India - Opportunities and challenges: Proceedings of an ICAR-ILRI international workshop, New Delhi, India, 31 January-1 February 2006 - Birthal, P.S.; Taneja, V.K.; Thorpe, W.R. (ILRI and NCAP, 2006)
This workshop was conducted to assess the development prospects of India's livestock in the context of changing global economic environment and its impact on the rural poor, and to suggest politically feasible and practical strategies and approaches for pro-poor growth in livestock production. An additional aim of the workshop was to explore possibilities of enhanced research collaboration between the national agricultural research systems (NARS) and ILRI. In the inaugural session of the workshop, summaries of the following two papers were presented to apprise the participants of the emerging trends in the livestock sector nationally and internationally, and to set the tone for the subsequent discussions. The papers were: 1. Livestock sector in India: Opportunities and challenges for smallholders PS Birthal and VK Taneja) and 2. Lessons from a changing world: Implications for livestock research and development by ILRI. The India paper provides a comprehensive overview of the livestock sector and brings out explicitly the importance of livestock in improving the wellbeing of the rural poor. The ILRI paper provides a synoptic view of the changing global environment and draws lessons for India and other developing countries to transform livestock production to the benefit of the poor.